Use of rituximab in the of immunoinflammatory rheumatic diseases combined with Graves' disease (autoimmune polyglandular syndrome in adults): case report and literature review - T. S. Panevin; E. G. Zotkin (Современная ревматология, 2024)
Rituximab (RTM) is a chimeric (murine and human) monoclonal antibody against B-lymphocytes (CD20). RTM is widely used in hematology for lymphoproliferative diseases and in rheumatology for rheumatoid arthritis, Sjögren's disease, some types of vasculitis and systemic connective tissue diseases. The administration of RTM is associated with a depletion of B-cells mediated by the regulation of apoptosis and cytotoxic effects via complement-dependent and antibody-dependent mechanisms. Considering the pathogenesis of autoimmune damage in Graves' disease (GD), an autoimmune thyroid disease associated with thyrotoxicosis, the use of RTM could be effective in this pathology. We present three patients with a combination of diffuse toxic goiter and rheumatic pathology treated with RTM; different outcomes of GD were observed.